2019
DOI: 10.1016/j.ebiom.2019.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Population-based inference of aminoglycoside resistance mechanisms in Escherichia coli

Abstract: Background: Interpretative reading of antimicrobial susceptibility test (AST) results allows inferring biochemical resistance mechanisms from resistance phenotypes. For aminoglycosides, however, correlations between resistance pathways inferred on the basis of the European Committee on Antimicrobial Susceptibility Testing (EUCAST) clinical breakpoints and expert rules versus genotypes are generally poor. This study aimed at developing and validating a decision tree based on resistance phenotypes determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…In addition, isolate No. 3/19 harboured the aac(6 )-Iid gene reported to confer gentamicin resistance [18]. Moreover, the WGS analysis showed the aph(3")-Ib, aph(3")-Id and aadA1 genes detected in one, one, and two isolates, respectively, as only detected streptomycin resistance determinants.…”
Section: Genotypic Antimicrobial Analysis In Silicomentioning
confidence: 99%
“…In addition, isolate No. 3/19 harboured the aac(6 )-Iid gene reported to confer gentamicin resistance [18]. Moreover, the WGS analysis showed the aph(3")-Ib, aph(3")-Id and aadA1 genes detected in one, one, and two isolates, respectively, as only detected streptomycin resistance determinants.…”
Section: Genotypic Antimicrobial Analysis In Silicomentioning
confidence: 99%
“…The use of gentamicin, in parenteral administration, has shown significant better infection outcomes involving some gram-negative bacteria such as Escherichia coli , Klebsiella pneumoniae , Pseudomonas aeruginosa , and was also efficient against some other strains such as Neisseria [ 5 , 6 , 7 ]. Gentamicin also proved to be efficient in bacterial septicemia, meningitis, peritonitis, endocarditis, pneumonia, urinary tract infections, or odontogenic infections [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently in EBioMedicine , Mancini and colleagues presented an Aminoglycoside Resistance Mechanism Inference Algorithm (ARMIA) for the inference of resistance mechanisms from inhibition zone diameters [7]. This algorithm uses ECOFFs for gentamicin, tobramycin and kanamycin as well as a working separator cut-off for amikacin.…”
mentioning
confidence: 99%
“…The results of this study showed that ARMIA-based inference of resistance mechanisms and WGS data were congruent in 96·3%. In contrast, there was a poor correlation between resistance mechanisms inferred using EUCAST CBPs/expert rules and WGS data (85·6%) [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation